2011
DOI: 10.1016/j.mrfmmm.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Variation in base excision repair capacity

Abstract: The major DNA repair pathway for coping with spontaneous forms of DNA damage, such as natural hydrolytic products or oxidative lesions, is base excision repair (BER). In particular, BER processes mutagenic and cytotoxic DNA lesions such as non-bulky base modifications, abasic sites, and a range of chemically distinct single-strand breaks. Defects in BER have been linked to cancer predisposition, neurodegenerative disorders, and immunodeficiency. Recent data indicate a large degree of sequence variability in DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 143 publications
(159 reference statements)
1
120
1
1
Order By: Relevance
“…This impairment in the recruitment and binding of BER proteins may then delay the DNA repair process or potentially lead to the accumulation of damaged DNA. Importantly, several of the OGG1 polymorphisms have been shown to have decreased catalytic activity, which may hinder the activation of PARP-1 and the early steps in the BER pathway (37,(51)(52)(53)(54). Indeed, both the R229Q and S326C have an impaired ability to activate PARP-1 compared with wild-type OGG1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This impairment in the recruitment and binding of BER proteins may then delay the DNA repair process or potentially lead to the accumulation of damaged DNA. Importantly, several of the OGG1 polymorphisms have been shown to have decreased catalytic activity, which may hinder the activation of PARP-1 and the early steps in the BER pathway (37,(51)(52)(53)(54). Indeed, both the R229Q and S326C have an impaired ability to activate PARP-1 compared with wild-type OGG1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both the R229Q and S326C have an impaired ability to activate PARP-1 compared with wild-type OGG1. This difference may be due to the fact that the S326C polymorphism exists as a dimer and has decreased enzymatic activity compared with wild-type and the R229Q polymorphism has decreased activity and is a thermolabile protein (37,(51)(52)(53)(54). Future work lies in further understanding the interplay between the OGG1 polymorphisms and PARP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left unrepaired, these lesions have the potential to alter cellular function and compromise the health of the organism, leading to degenerative diseases, cancer, and premature aging (1)(2)(3)(4)(5). Consequently, interindividual variations in DNA repair capacity (DRC) are thought to contribute to the fact that people have different susceptibilities to these diseases (6)(7)(8)(9)(10). Furthermore, the efficacy of cancer chemotherapy with DNA-damaging agents depends on the DRC of the targeted cells (11).…”
mentioning
confidence: 99%
“…Further site-directed mutagenesis studies on APEl active site using N68A, D70A, Y171F, D210N, F266A, D308A, and H309S confirmed that APEl shares the same active site for both abasic DNA incision activities and RNA cleaving activity (Kim et al 201 lb). However, these APEl mutants retained their ability to bind the RNA substrate, required 2'-OH on the sugar for cleavage, and did not require presence of a divalent ion unlike abasic DNA incision activity of APEl (Kim et al 2011). Therefore, it was postulated that although APEl shares the same active site, they may have different mechanisms for cleaving RNA, abasic ssRNA, and abasic DNA.…”
Section: Discovery Of Endoribonuclease Activity Of Apel and Its Role mentioning
confidence: 99%